Efektivitas Pemberdayaan Masyarakat Melalui Program Rumah Tidak Layak Huni (RUTILAHU) di Kota Surabaya Guna Meningkatkan Kesejateraan Masyarakat - Sherly Novita Sary; M. Kendry Widiyanto; Dida Rahmadanik (Jurnal Relasi Publik, 2024)
This research was conducted with the aim of analyzing the effectiveness of community empowerment through the uninhabitable housing (Rutilahu) program in the city of Surabaya to improve community welfare. This research uses qualitative research, with data collection techniques through observation, interviews and documentation. The research results show that the effectiveness of community empowerment through the uninhabitable housing (Rutilahu) program in the city of Surabaya to improve community welfare has been effective in several aspects but still has shortcomings in the socialization aspect of the program. Even though the program has been successful in achieving targets, there are still shortcomings in socializing the program to the community. The large number of people who do not know about this program shows that outreach efforts need to be increased to be more optimal. By conducting regular direct outreach, going around to every sub-district and RW to hold outreach and invite the public so that people also know about this program.